If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7m + -5n = 0 Solving 7m + -5n = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '5n' to each side of the equation. 7m + -5n + 5n = 0 + 5n Combine like terms: -5n + 5n = 0 7m + 0 = 0 + 5n 7m = 0 + 5n Remove the zero: 7m = 5n Divide each side by '7'. m = 0.7142857143n Simplifying m = 0.7142857143n
| 5x+3=-30+2x | | 7(z-2)=-6z-8+13z | | 50h=190-45h | | b/4+1/7=19 | | 1/4y=-5x+7 | | 3(u-1)-1=-3(-4u+6)-u | | 1/4(3x-1)=2(x-2) | | x/9x=2/3 | | 29/5=k-1/5(-10k-4) | | 4/3x=44 | | 2(x-3)=5(2x+6) | | -6(9x-8)=425 | | (16+a)+11= | | 18+2x=9x+4 | | 2(x+5)=6x+10-4x | | 5(t+3)+9=3t+(-6)+6 | | 3/2(y+2)=g | | 2/3(3x-6)=10 | | 6[3-(4+4x)]=-8+2(1-14x) | | 21x+7=3x+16 | | 4-5x=-26 | | 4/p=16/5 | | 9(m+1)-6m=3m+6 | | 2-5/16 | | 2x8-2+6/3=0 | | 3-4(6+11p)=-7p-58 | | 8x-3y=32 | | 5-8x=19-10x | | -2(8u-9)+6u=5(u+6) | | 4x+14=3x+6 | | -x-9=-6x+36 | | 4(a-2)+4=2a-6 |